2015
DOI: 10.5811/westjem.2015.4.25760
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Decision Support Implementation in Emergency Department Vancomycin Dosing

Abstract: IntroductionThe emergency department (ED) plays a critical role in the management of life-threatening infection. Prior data suggest that ED vancomycin dosing is frequently inappropriate. The objective is to assess the impact of an electronic medical record (EMR) intervention designed to improve vancomycin dosing accuracy, on vancomycin dosing and clinical outcomes in critically ill ED patients.MethodsRetrospective before-after cohort study of all patients (n=278) treated with vancomycin in a 60,000-visit Midwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…The most common interventions described were patient or provider education and guideline or clinical pathway implementation alone or in combination with other interventions. 19-47 A number of these studies found a significant improvement in surrogate outcomes such as adherence to guidelines or appropriateness of antimicrobial prescribing 26,28,32,35,36,38,42,43,45-47 and decreased antimicrobial use. 21,24,30,44,45 Five studies evaluating implementation of guidelines or clinical pathways alone 19,20 or in combination with education 28,40 or monitoring and feedback 33 demonstrated statistically significant improvements in clinical outcomes, including hospital length of stay, 19,20,28,40 ED length of stay, 33 admission of low risk patients to hospital, 20 admission to the intensive care unit, 28 readmission to ED, 28,40 and mortality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common interventions described were patient or provider education and guideline or clinical pathway implementation alone or in combination with other interventions. 19-47 A number of these studies found a significant improvement in surrogate outcomes such as adherence to guidelines or appropriateness of antimicrobial prescribing 26,28,32,35,36,38,42,43,45-47 and decreased antimicrobial use. 21,24,30,44,45 Five studies evaluating implementation of guidelines or clinical pathways alone 19,20 or in combination with education 28,40 or monitoring and feedback 33 demonstrated statistically significant improvements in clinical outcomes, including hospital length of stay, 19,20,28,40 ED length of stay, 33 admission of low risk patients to hospital, 20 admission to the intensive care unit, 28 readmission to ED, 28,40 and mortality.…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly reported additional resources were personnel, including dedicated ID specialists, pharmacists, nurses, specialists in informatics, and AMS teams for the ED, 18,19,24,26,27,32,35,36,[47][48][49][51][52][53][54][55][56][57][58] and use of information technology (IT), including computerized order entry, electronic medical records, computer decision support, and automated dispensing cabinets. 18,35,38,42,46,49,52,54,59,60…”
Section: Facilitators and Barriersmentioning
confidence: 99%
“…Faine et al 29 evaluated the effect of CPOE with CDSS on the rate of inappropriate dosing in the ED. This study showed that the rate of inappropriate dosing significantly decreased from 34.3% to 24% ( P value = 0.07).…”
Section: Resultsmentioning
confidence: 99%
“… 3 , 40 Medication dosing can be complex, particularly when weight based, and incorporation of CDS or calculators can improve dosing, although it may have a limited impact. 4 Similarly, CDS based on patient-specific factors can reduce prescribing of excessive doses and may improve the percentage of patients who reach cholesterol goals. 21 23 The same can also be seen with alerts which are customized by an institution to produce better alert sensitivity and specificity.…”
Section: Discussion Of Impactsmentioning
confidence: 99%
“… 3 , 22 Clinical decision support integrated into hospital systems such as those for medication dosing may improve dosing, but it may not always result in any clinical improvements and in some cases may result in increases in inappropriate therapy or duplicate medication orders. 4 , 8 , 15 , 18 , 30 , 31 Although it may not always be effective, in some cases, it can have an impact not only on patient safety but also on length of stay, percentage of patients who reach low-density lipoprotein cholesterol goals, and other metrics for patient outcomes and hospital spending. 17 , 23 Despite not being directly tied to patient outcomes, CDS may also be used to facilitate medication reconciliation for inpatient providers.…”
Section: Applicationsmentioning
confidence: 99%